2016
DOI: 10.1111/aos.13323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blue‐blocking and neutral intraocular lenses on circadian photoentrainment and sleep one year after cataract surgery

Abstract: Blue-blocking IOLs increased sleep efficiency but lowered nocturnal melatonin secretion compared with neutral IOLs. Cataract surgery improved the response of ipRGCs and sleep quality. However, the effect of cataract surgery on sleep quality may be unrelated to circadian photoentrainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
(60 reference statements)
1
22
0
2
Order By: Relevance
“…Even though photoreception is improved by cataract surgery, its impact on circadian rhythm and sleep is still unclear. In other words, whether improved sleep quality reflects increased life quality due to the cataract surgery or related to changes in the circadian rhythm is not known yet (Brondsted et al 2015(Brondsted et al , 2016. Two patients with NTG had undergone selective laser trabeculoplasty in the consensual eye, which might influence pupil metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Even though photoreception is improved by cataract surgery, its impact on circadian rhythm and sleep is still unclear. In other words, whether improved sleep quality reflects increased life quality due to the cataract surgery or related to changes in the circadian rhythm is not known yet (Brondsted et al 2015(Brondsted et al , 2016. Two patients with NTG had undergone selective laser trabeculoplasty in the consensual eye, which might influence pupil metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying assumption is that the retina might be protected from phototoxic blue light, purported to be involved in age‐related macular degeneration (Cruickshanks, Klein, Klein, & Nondahl, 2001). Although visual function between BB and UV‐only IOLs might be comparable (Mester, Holz, Kohnen, Lohmann, & Tetz, 2008; but see also Steinemann et al, 2019) for differences between these IOLs, the reduced transmittance of blue light, which is pivotal to circadian photoentrainment, has led to concern that BB IOLs may adversely impact circadian rhythmicity (Brondsted et al, 2017; Chellappa et al, 2019). Taken together, the benefits of specific IOLs for circadian rhythmicity and cognitive function still remain to be fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated circadian photoentrainment and sleep following implantation of blue-blocking intraocular lenses (IOLs). 54,55 The authors reported that patients with blue-blocking IOLs showed no differences in any ipRGC-driven pupil responses, sleep-specific actigraph measures, melatonin onset or PSQI scores compared to subjects with neutral IOLs after 1 year. The authors did find that peak melatonin concentration was 50% lower in the blue-blocking IOL group compared to the neutral IOL group.…”
Section: Discussionmentioning
confidence: 99%